NEUROPROTECTIVE EFFECT OF ANACARDIUM OCCIDENTALE (CASHEW APPLE FRUIT) AGAINST ALUMINUM TOXICITY: AN EXPERIMENTAL STUDY ON COGNITIVE DYSFUNCTION AND BIOCHEMICAL ALTERATIONS IN RATS - P, Bhagyasree; G, KALYANI (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Objective: To study the protective role of fruit extract of Anacardium occidentale (cashew apple) in aluminum-induced cognitive dysfunction and oxidative damage in albino rat, and to explore the neuroprotective effect of A. occidentale represented by behavior and memory tests. Methods: Male Wistar rats (30) were divided into 5 groups of 6 rats each. Group I received normal saline. Group II was administered orally with aluminum chloride (100 mg/kg). Group III received rivastigmine 0.3 mg/kg body orally. Groups IV and V were administered with A. occidentale 200 and 400 mg/kg along with aluminum chloride of 100 mg/kg orally after 1 hr interval. The study was carried out for 42 days (6 weeks). The behavioral assessment was performed using Rota-rod apparatus and Elevated plus maze and Biochemical parameters from brain homogenate such as acetylcholinesterase activity, total protein, lipid peroxidation malondialdehyde, superoxide dismutase (SOD), catalase, and glutathione reductase (GR) were estimated. All the data were analyzed using one-way analysis of variance followed by Tukey’s multiple comparison test. Results: The % reduction of acetylcholinesterase, GR observed in A.O (400 mg/kg) dose as compared with that of standard drug was found to be 87.5% and 89%, respectively, whereas % reduction of catalase and SOD observed in A.O (400 mg/kg) dose as compared with that of standard drug was found to be 97% and 99%, respectively. Conclusion: This study demonstrates A. occidentale fruit has a neuroprotective effect against aluminum-induced behavioral changes. Keywords: Occidentale, Neuroprotective, Alzheimer’s disease, Aluminum.